An EAPCI Expert Consensus Document on Ischaemia with Non-Obstructive Coronary Arteries in Collaboration with European Society of Cardiology Working Group on Coronary Pathophysiology & Microcirculation Endorsed by Coronary Vasomotor Disorders International Study Group. (6th July 2020) - Kunadian, Vijay; Chieffo, Alaide; Camici, Paolo G; Berry, Colin; Escaned, Javier; Maas, Angela H E M; Prescott, Eva; Karam, Nicole; Appelman, Yolande; Fraccaro, Chiara; Louise Buchanan, Gill; Manzo-Silberman, Stephane; et al.
Abstract: This consensus document, a summary of the views of an expert panel organized by the European Association of Percutaneous Cardiovascular Interventions (EAPCI), appraises the importance of ischaemia with non-obstructive coronary arteries (INOCA). Angina pectoris affects approximately 112 million people globally. Up to 70% of patients undergoing invasive angiography do not have obstructive coronary artery disease, more common in women than in men, and a large proportion have INOCA as a cause of their symptoms. INOCA patients present with a wide spectrum of symptoms and signs that are often misdiagnosed as non-cardiac leading to under-diagnosis/investigation and under-treatment. INOCA can result from heterogeneous mechanism including coronary vasospasm and microvascular dysfunction and is not a benign condition. Compared to asymptomatic individuals, INOCA is associated with increased incidence of cardiovascular events, repeated hospital admissions, as well as impaired quality of life and associated increased health care costs. This consensus document provides a definition of INOCA and guidance to the community on the diagnostic approach and management of INOCA based on existing evidence from research and best available clinical practice; noting gaps in knowledge and potential areas for further investigation. Graphical Abstract: